2021
DOI: 10.1289/ehp8584
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Air Pollution Exposure in the United States by Race/Ethnicity and Income, 1990–2010

Abstract: Background: Few studies have investigated air pollution exposure disparities by race/ethnicity and income across criteria air pollutants, locations, or time. Objective: The objective of this study was to quantify exposure disparities by race/ethnicity and income throughout the contiguous United States for six criteria air pollutants, during the period 1990 to 2010. Methods: We quantified exposure disparities among racial/ethnic groups (non-Hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
156
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(170 citation statements)
references
References 50 publications
9
156
2
3
Order By: Relevance
“…A smaller body of literature documents disparities nationwide for the United States ( Bell and Ebisu 2012 ; Clark et al. 2014 , 2017 ; Liu et al. 2021 ; Miranda et al.…”
Section: Introductionmentioning
confidence: 99%
“…A smaller body of literature documents disparities nationwide for the United States ( Bell and Ebisu 2012 ; Clark et al. 2014 , 2017 ; Liu et al. 2021 ; Miranda et al.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated that people of color in the United States are typically exposed to higher levels of air pollution than White Americans, regardless of income. 1 , 2 , 3 This persistent inequity appears to increase vulnerability to pollution-related disease among these groups. 4 The authors of a new paper in Environmental Health Perspectives explored whether health disparities might be reduced if federal regulators considered differences in the association between air pollution exposure and mortality across different racial/ethnic groups.…”
mentioning
confidence: 99%
“…Liu et al. ( 2021 ) built on this literature in a few important ways. They included all criteria air pollutants in a single analysis and looked at multiple years (1990, 2000, and 2010) across the entire contiguous United States.…”
mentioning
confidence: 99%
“…In addition, as articulated by Liu et al. ( 2021 ), air pollution disparities analyses are generally dependent on publicly available census data, which creates limitations in moving beyond general racial/ethnic categories (e.g., the Hispanic category, which encompasses numerous countries of origin, racial identities, and nativity statuses). Census data also limit the ability to conduct truly intersectional analyses or to incorporate attributes, such as sexual orientation or gender identity, that are underrepresented in the environmental justice literature ( Collins et al 2017 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation